POWER QUALITY INVESTIGATION OF SINGLE PHASE GRID-CONNECTED INVERTER OF PHOTOVOLTAIC SYSTEM - Alawasa, Khaled M.; Al-Odienat, Abdullah I. (ITB Journal Publisher, LPPM ITB, 2019)
There is a growing demand for renewable energy resources in countries all around the world. Among renewable energy resources, solar energy is a prominent and promising alternative to meet future electricity needs. Recently, the renewable energy regulations in Jordan have been modified to allow customers to install their own photovoltaic (PV) generators to cover their full energy consumption. This study investigated the power quality profile of single-phase grid-connected PV system in a typical Jordanian low voltage electrical system. The following electrical parameters were monitored: voltage, current, harmonics contents, total harmonics distortion (THD), active power, reactive power, and power factor. Detailed investigations and analyses were made.